Vision and difference femininity, feminism, and histories of art - Pollock, Griselda (Routledge, 1988)
Griselda Pollock provides concrete historical analyses of key moments in the formation of modern culture to reveal the sexual politics at the heart of modernist art. Crucially, she not only explores a feminist re-reading of the works of canonical male Impressionist and Pre-Raphaelite artists including Edgar Degas and Dante Gabriel Rossetti, but also re-inserts into art history their female contemporaries - women artists such as Berthe Morisot and Mary Cassatt. Pollock discusses the work of women artists such as Mary Kelly and Yve Lomax, highlighting the problems of working in a culture where the feminine is still defined as the object of the male gaze.
Section: 239 p. : ill. ; 24 cm
Keywords: arts; corps; cours; discipline; europe; femmes* artistes; har4600; har4610; histoire de l'art; histoire et politique; premier cycle; représentation des femme*; régions géographiques; thématiques

Old mistresses: Women, art and ideology - Parker, Rozsika; Pollock, Griselda (Pantheon Books, 1981)
How was it possible, by the later twentieth century, to have erased women as artists from art history so comprehensively that the idea of 'the artist' was exclusively masculine? Why was this erasure more radical in the twentieth century than ever before? Why is everything that compromises greatness in art coded as 'feminine'? Has the feminist critique of Art History yet effected real change? With a new Preface by Griselda Pollock, this new edition of a truly groundbreaking book offers a radical challenge to a women-free Art History. Parker and Pollock's critique of Art History's sexism leads to expanded, inclusive readings of the art of the past. They demonstrate how the changing historical social realities of gender relations and women artists' translation of gendered conditions into their works provide keys to novel understandings of why we might study the art of the past. They go further to show how such knowledge enables us to understand art by contemporary artists who are women and can contribute to the changing self-perception and creative work of artists today.
Keywords: LGBTQIA2+; approches et analyses; art féministe; arts; cours; discipline; fem1000; genre; har4600; histoire de l'art; histoire et politique; identités LGBTQIA2+; premier cycle; sexisme; stéréotypes; systèmes d'oppressions; thématiques